A case of Wiskott — Aldrich syndrome in an infant - E. V. Churyukina; E. V. Koreeva; O. S. Selezneva (Аллергология и Иммунология в Педиатрии, 2023)
Wiskott — Aldrich syndrome (WAS) is a rare, X-linked combined disease with immunodeficiency caused by mutations in the WAS gene that encodes the WAS protein (WASp). Manifestations range from a relatively mild form of the disease (intermittent X-linked thrombocytopenia), characterized by thrombocytopenia with or without minor immunodeficiency, to a severe form with deep immunodeficiency, episodes of bleeding, the development of autoimmunity and an increased risk of malignancy. Many patients have intermediate degrees of severity. It is precisely this heterogeneity in the clinical spectrum that makes it difficult to make a primary diagnosis of WAS. The article presents a clinical case of primary immunodeficiency detected in a 2-month-old child.